The Other Girl - Spindler, Erica 1957- (Thorndike, Maine : Center Point Large Print, 2017)
"The ritualistic murder of a college professor sends a small town cop back into the trauma she thought she'd put behind her"--
Keywords: Murder -- Fiction -- Investigation; Women detectives -- Fiction; Policewomen -- Fiction; Large type books; FICTION / Suspense; Suspense fiction; Mystery fiction